Pyrite FeS2@C nanorods as smart cathode for sodium ion battery with ultra-long lifespan and notable rate performance from tunable pseudocapacitance. (10th January 2018) - Lu, Zhenxiao; Wang, Nana; Zhang, Yaohui; Xue, Pan; Guo, Meiqing; Tang, Bin; Bai, Zhongchao; Dou, Shixue
Abstract: Sodium ion batteries (SIBs) are a promising replacement for the widely prevalent Li-ion batteries (LIBs) as an efficient energy storage technology. Development of electrode materials with high energy density and high power density is the key to achieving high performance SIBs. Here, we demonstrate a high-capacity and high-rate SIB cathode which is made of one-dimensional FeS2 nanorods, where an extrinsic pseudocapacitance contribution is found and verified by cyclic voltammetry. The carbon coated FeS2 nanorods exhibit ultra-long lifespan (9000 cycles), high reversible capacity (506.9 mAh g −1  at 500 mA g −1 ), and outstanding rate capability (140 mAh g −1  at 20 A g −1 ). Graphical abstract: Highlights: A facile approach is proposed to fabricate FeS2 @C nanorods for sodium ion battery. The FeS2 @C deliverers ultra-long cycling stability and notable rate performance. Pseudocapacitance behavior of FeS2 @C in SIBs was analyzed and quantified.